Varonia Exclusive Sdn. Bhd / Nur Farah Adriana Ahmad Faizal - Ahmad Faizal, Nur Farah Adriana (2021)
The following is the report to my precious Fundamentals of Entrepreneurship ENT 300 lecturer, Madam Nur Haslina Binti Ramli. This assignment is regarding the individual case study assignment. It requires me to identify one of the entrepreneurs. It also requires having an interview session with the entrepreneur. The entrepreneur that I have chosen is Madam Nor Zaini Binti Yusof. She is the founder of Varonia Exclusive Sdn. Bhd. The type of business is a sole proprietorship. The production runs at Gelugor, Penang Island. The interview went smoothly as she gave her full cooperation. We had the interview session on the WhatsApp application. I get her phone number through his son, Mohammad Shafiq, as he is my friend. I texted Madam Nor Zaini Binti Yusof on 26th October 2021, and she replied to me on 1st November 2021. It took a week for her to reply to me since she had a lot of things to be done that week. Madam Nor Zaini Binti Yusof gives me all the information that I needed. I give the questions in a point form and she just needs to fill in the blank which is quite simple for me to understand the information. Based on the interview session, I get to know the company’s profile in more detail. I also get to know the founder’s profile. Furthermore, I can determine which entrepreneurial competencies that Madam Nor Zaini Binti Yusof practice in her company. Some of the entrepreneurial competencies that Madam Nor Zaini uses in her company are opportunity seeking, risk-taking, problem-solving, systematic planning, and concern for a high-quality product.